Enhanced photon collection of high surface area carbonate-doped mesoporous TiO2 nanospheres in dye sensitized solar cells. (May 2018) - Ganesh, R. Sankar; Navaneethan, M.; Ponnusamy, S.; Muthamizhchelvan, C.; Kawasaki, S.; Shimura, Y.; Hayakawa, Y.
Graphical abstract: Highlights: Carbonate-doped mesoporous TiO2 showed enhanced DSSC efficiency (5.4%). Carbonate-doped TiO2 indicated higher surface area and incident photon conversion efficiency. Carbonate-doped TiO2 showed lower resistance and longer life time. Abstract: Carbonate-doped mesoporous TiO2 nanospheres with anatase phase were　successfully synthesized by the simple solvothermal method. The synthesized nanospheres were monodispersed and composed of particles having the size of 10–15 nm. Scanning transmission electron microscopy (STEM) analysis showed nanosphere with large number particles. STEM-mapping clearly showed that Ti, O, and C were homogeneously distributed. Incorporation of carbonate in TiO2 was confirmed by XPS analysis. The peak at 284.3 eV was assigned to CO and indicated the formation TiOC structure due to carbonate doping in TiO2 lattice. Dye-sensitized solar cells (DSSCs) containing the nanospheres were fabricated by spray coating technique using N719 dye. Carbonate-doped mesoporous TiO2 showed enhanced DSSC efficiency (5.4%) compared to undoped (3.4%) and commercially available TiO2 (P25) (2.4%). It indicated (1) higher surface area and incident photon conversion efficiency, (2) lower resistance and longer life time compared with undoped TiO2 .